DIFFERENTIAL QUADRATURE METHOD: APPLICATION TO INITIAL- BOUNDARY-VALUE PROBLEMS - Tomasiello, S. (Journal of sound and vibration, 1998)
Two non-linear dynamical systems have been considered. In both cases, the governing equation of motion is reduced to two second-order non-linear non-autonomous ordinary differential equations using the differential quadrature method with a careful distribution of sampling points. To check the numerical results, a comparison with those obtained using the Galerkin approach is proposed.